Relating ring width of Mediterranean evergreen species to seasonal and annual variations of precipitation and temperature - Nijland, W; Jansma, E; Addink, E a.; Domínguez Delmás, M; De Jong, S M (Biogeosciences, 2011)
Plant growth in Mediterranean landscapes is limited by the typical summer-dry climate. Forests in these areas are only marginally productive and may be quite susceptible to modern climate change. To improve our understanding of forest sensitivity to annual and seasonal climatic variability, we use tree-ring measurements of two Mediterranean evergreen tree species: Quercus ilex L. and Arbutus unedo L. We sampled 34 stems of these species on three different types of substrates in the Peyne study area in southern France. The resulting chronologies were analysed in combination with 38 yr of monthly precipitation and temperature data to reconstruct the response of stem growth to climatic variability. Results indicate a strong positive response to May and June precipitation, as well as a signiﬁcant positive inﬂuence of early-spring temperatures and a negative growth response to summer heat. Comparison of the data with more detailed productivity measurements in two contrasting years conﬁrms these observations and shows a strong productivity limiting effect of low early-summer precipitation. The results show that tree-ring data from Q.ilex andA.unedo can provide valuable information about the response of these tree species to climate variability, improving our ability to predict the effects of climate change in Mediterranean ecosystems.
Keywords: climate variability (voyant); Growth; Mediterranean evergreen species; ring width

Radial variation of wood density components and ring width in cork oak trees - Knapic, S; Louzada, J L; Leal, S; Pereira, H (Annals of forest science, 2007)
– The radial variation of ring width and wood density was studied in cork oaks (Quercus suber) using microdensitometry. The observations were made in young never debarked cork oaks (30–40 years of age) and in mature trees under cork production (37–60 years of age). The cork oak wood is very dense (mean ring density 0.86 g.cm−3 , between 0.79 g.cm−3 and 0.97 g.cm−3 ) with a small intra-ring variability (mean earlywood density 0.80 g.cm−3 and latewood density 0.90 g.cm−3 ). The density components decreased from pith to bark more rapidly until the 15th ring, and then only slightly. There were no signiﬁcant diﬀerences in the mean density components between never debarked trees and trees under cork production but their outwards decrease was accentuated in the never debarked trees. The annual growth was high, with a ring width mean of 3.9 mm (4.2 mm in the ﬁrst 30 years) and the latewood represented 57% of the annual growth.
Keywords: Cork oak; Density; latewood; Quercus suber; ring width